PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Maryamah Maryamah; Iis Nurasiah; Irna Khaleda Nurmeta (STKIP Subang, 2023)
The purpose of this study was to determine the increase in students' science learning outcomes through the application of the guided inquiry learning model. This research was conducted at one of the public elementary schools in the Ciracap sub-district, Sukabumi district. This research focuses on VB class students for the 2022/2023 school year. The time of the study was from January 19 to May 30, 2023 with 25 student subjects, consisting of 13 male students and 12 female students. This study used the Kemmis and Mc Taggart classroom action research (CAR) model. This research was conducted in 2 cycles. Each cycle consists of two meetings. Each cycle consists of four stages, namely: (1) planning, (2) action, (3) observation/evaluation, (4) reflection. The data collection method in this study used observation sheets and evaluation tests. The results of this study showed an increase in students' science learning outcomes, in cycle I the average student score was 78 with classical completeness 72% in the sufficient category and in cycle II the average student score increased to 85 with classical completeness 92% in the very good category. Thus it can be concluded that, through the Guided Inquiry learning model it can improve science learning outcomes in class VB students at SD Negeri Pasirgoong, Ciracap District, Sukabumi Regency, Academic Year 2022/2023.